2007
DOI: 10.1292/jvms.69.985
|View full text |Cite
|
Sign up to set email alerts
|

Propionate Tolerance Test for Determination of Insulin Secretion in a Hyperglycemic japanese Black Steer

Abstract: ABSTRACT. A propionate tolerance test (PTT) was used to determine the pathophysiology of a Japanese Black steer with hyperglycemia. In the hyperglycemic steer, a low insulin secretion was confirmed by a glucose tolerance test (GTT), so that the hyperglycemic steer was diagnosed as insulin-dependent diabetes mellitus. Although the plasma insulin concentration in the control cattle increased in response to propionate stimulation, a low insulin response to PTT was observed in the diabetic steer. The fact that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Propionate has been shown to be an insulin secretagogue in addition to glucose (Sano et al 1993), and it is likely that the high-fat diet, in general, reduced b-cell responsiveness to major secretagogues such as glucose and propionate. Interestingly, propionate has also been used as a diagnostic tool in ruminants to identify diabetic animals (Takasu et al 2007), where a reduced insulin response was observed just as we had observed in the present study. The reduced b-cell responsiveness would also be an important factor explaining why the HCHF lambs even 2 h after injection continued to have markedly elevated glucose concentrations compared with the NORM lambs.…”
Section: Discussionsupporting
confidence: 79%
“…Propionate has been shown to be an insulin secretagogue in addition to glucose (Sano et al 1993), and it is likely that the high-fat diet, in general, reduced b-cell responsiveness to major secretagogues such as glucose and propionate. Interestingly, propionate has also been used as a diagnostic tool in ruminants to identify diabetic animals (Takasu et al 2007), where a reduced insulin response was observed just as we had observed in the present study. The reduced b-cell responsiveness would also be an important factor explaining why the HCHF lambs even 2 h after injection continued to have markedly elevated glucose concentrations compared with the NORM lambs.…”
Section: Discussionsupporting
confidence: 79%
“…The limit of detection was 0.025 ng/ml and the intra- and inter-assay CVs were 3.3% and 8.7%, respectively, at 0.50 ng/ml. This assay has been used to measure changes in blood insulin concentrations in Japanese Black steer before and after glucose treatment [ 22 ].…”
Section: Methodsmentioning
confidence: 99%